Clinical Manifestations of Iscehaemic and Reperfusion Injury - Pradian, Erwin; , Rizki; Maskoen, Tinni Trihartini (Perdatin Pusat, 2015)
Although restoration of blood low to an ischaemic organ is essential to prevent irreversible tissue injury, reperfusionper se may result in a local and systemic inlammatory response that may augment tissue injury in excess of thatproduced by ischaemia alone. Cellular damage after reperfusion of previously viable ischaemic tissues is deinedas ischaemia-reperfusion (I-R) injury. I-R injury is characterized by oxidant production, complement activation,leucocyte endothelial cell adhesion, platelet-leucocyte aggregation, increased microvascular permeability anddecreased endothelium-dependent relaxation. In its severest form, I-R injury can lead to multiorgan dysfunctionor death. Although our understanding of the pathophysiology of I-R injury has advanced signiicantly in the lastdecade, such experimentally derived concepts have yet to be fully integrated into clinical practice. Treatment ofI-R injury is also confounded by the fact that inhibition of I-R-associated inlammation might disrupt protectivephysiological responses or result in immunosuppression. Thus, while timely reperfusion of the ischaemic areaat risk remains the cornerstone of clinical practice, therapeutic strategies such as ischaemic preconditioning,controlled reperfusion, and anti-oxidant, complement or neutrophil therapy may signiicantly prevent or limit I-Rinducedinjury in humans.